Traduire l’archive : voix et silences dans le Canto 8 des Cantos d’Ezra Pound - Charlotte Estrade (Sillages Critiques)
Canto 8 is the first of Ezra Pound’s historical Cantos, providing quotations, translations and a recontextualisation of personal archives, i.e. the correspondence of Sigismundo Malatesta. This enables Pound to question and – he hopes – correct the way historical discourse and knowledge are constructed, and to produce an ideologically-charged poem which is also a monument illustrating a dialogue between various epochs. Meanwhile, Pound’s writing attempts a new definition of the statuses, functions and possible limits of both poetry and archives. The way archives are rewritten suggest a complex dialectic: can a historical source become poetry and how? Can poetry produce or be a valid form of historical discourse?